Health Needs of Adults with Intellectual Disability Relevant for the Family Physician - Joav Merrick; Isack Kandel; Mohammed Morad (The Scientific World Journal)
People with developmental disability, mental retardation, or intellectual disability are living longer and becoming prone to age-related health problems and diseases of old age much like the general population. This worldwide trend is also seen in Israel, where today 39.8% of persons with intellectual disability in residential care are 40 years old and above. There is a need for service and staff providers to receive training; a need for more research and better service for this aging population. This review presents health concerns for older persons with different levels of intellectual disability, health concerns in persons with Down syndrome, and persons with epileptic seizures and cerebral palsy in relation to general practice and family medicine. The review is concluded with recommendations on health and aging in adults with intellectual disabilities and the call for formalized training in the topic for specialists in family medicine.